2008
DOI: 10.1039/b802478m
|View full text |Cite
|
Sign up to set email alerts
|

Trace element analysis of silicon nitride powders by direct solid sampling graphite furnace atomic absorption spectrometry

Abstract: A graphite furnace atomic absorption spectrometry method using direct solid sampling has been developed for the determination of Cr, Cu, Fe, K, Mn, Sb and Zn in powdered silicon nitride. Although during the atomization of all analytes excluding Zn, conversion of silicon nitride into silicon and silicon carbide was taking place and its essential part vaporized in the form of different species, no problems occurred with background correction. Calibration could be carried out by using calibration curves obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A direct solid sampling introduction method has been applied by de Mattos and co-workers who determined seven impurities (Cr, Cu, Fe, K, Mn, Sb and Zn) in silicon nitride powders by GFAAS. 374 No problems were observed with the background correction methods and calibration could be achieved using aqueous standards. For the determination of Fe, it was necessary to coat the platform with an extra layer of graphite powder in order to achieve quantitative vaporization and to increase the lifetime of the platform.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…A direct solid sampling introduction method has been applied by de Mattos and co-workers who determined seven impurities (Cr, Cu, Fe, K, Mn, Sb and Zn) in silicon nitride powders by GFAAS. 374 No problems were observed with the background correction methods and calibration could be achieved using aqueous standards. For the determination of Fe, it was necessary to coat the platform with an extra layer of graphite powder in order to achieve quantitative vaporization and to increase the lifetime of the platform.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Under the use of Pd and Mg salts as modifier, both techniques were found to deliver accurate results (40). With direct solids sampling GFAAS and under the use of background correction and graphite platform atomization, Cr, Cu, Fe, K, Mn, Sb, and Zn could be reliably determined in silicon nitride powders as well (41).…”
Section: Atomic Absorption Spectrometrymentioning
confidence: 99%
“…In the last two decades several analytical procedures have been developed for the direct determination of elements at the trace level in numerous refractory materials, such as aluminium oxide, 4,5 boron nitride, 6,7 silicon carbide [8][9][10][11][12] and silicon nitride. 13 However, until now only three studies focused on the direct analysis of boron carbide powders. [14][15][16] K antor et al 14 reported on the determination of trace metals in industrial boron carbide powders by direct current arc optical emission spectrometry (DC-arc-OES).…”
Section: Introductionmentioning
confidence: 99%